Vintaik kalaiñan̲in̲ uruvac cittiram (Cantiyā Patippakam, 2013)
Novel on social themes
Novel. - In Tamil-Schrift, Tamil. - Title on t.p. verso in roman: Vinthaik kalaignanin uravach chiththiram
Keywords: Tamil fiction